Organocatalytic cascade aza-Michael/hemiacetal reaction between disubstituted hydrazines and α,β-unsaturated aldehydes: Highly diastereo- and enantioselective synthesis of pyrazolidine derivatives - Geng, Zhi-Cong; Chen, Jian; Li, Ning; Huang, Xiao-Fei; Zhang, Yong; Zhang, Ya-Wen; Wang, Xing-Wang (Beilstein Journal of Organic Chemistry, 2012)
The catalytic synthesis of nitrogen-containing heterocycles is of great importance to medicinal and synthetic chemists, and also a challenge for modern chemical methodology. In this paper, we report the synthesis of pyrazolidine derivatives through a domino aza-Michael/hemiacetal sequence with chiral or achiral secondary amines as organocatalysts. Thus, a series of achiral pyrazolidine derivatives were obtained with good yields (up to 90%) and high diastereoselectivities (>20:1) with pyrrolidine as an organocatalyst, and enantioenriched pyrazolidines are also achieved with good results (up to 86% yield, >10/1 regioselectivity, >20:1 dr, 99% ee) in the presence of (S)-diphenylprolinol trimethylsilyl ether catalyst.
Keywords: aza-Michael; domino; hydrazine; organocatalysis; pyrazolidine